Monitoring of River Estuary Turbidity using Satellite Image Analysis and Its Correlation to Rainfall (A Case Study of the Krueng River in Aceh, Indonesia) - Abdulah Mujahid Hamdan; Muhammad Tri Fajar; Rafiza Mustaqin; Mulyadi Abdul Wahid; Rahmad Maulana; Muhammad Fadhil Zainuddin (Lambung Mangkurat University Press, 2022)
Activities along the Krueng Aceh river such as port activities, fisheries, ship breeding, tourist attractions, market activities and settlements cause a lot of domestic waste in the environment around the river and affect river clarity and increase the concentration of turbidity. High turbidity in rivers can affect the entry of light into the waters because light has an important role in the photosynthesis process. The method of monitoring water quality can be done by remote sensing because it has several advantages such as being able to carry out measurements on a larger scale for a long time, relatively quickly, and reducing the amount of costs incurred. Monitoring the Krueng Aceh River is carried out using remote sensing technology using Sentinel-2 imagery. This study aims to obtain the value of the distribution of turbidity by analyzing satellite imagery and its correlation with rainfall, and to determine the value of the distribution of turbidity, Total Suspended Solid (TSS), Total Dissolved Solid (TDS), and Power of Hydrogen (pH) in the Krueng Aceh River. The results showed that sentinel-2 image analysis got the lowest turbidity on September 6, 2021, which was -0.992424, and the highest on October 5, 2019 which was 0.248641. The distribution of water quality is known to have the highest turbidity concentration obtained at sampling location point 1, which was 107.9 NTU. The highest concentration of TSS was found at sampling locations 1, 4, and 7, which was 400 mg/l. The highest TDS concentration was found at point location 1, which was 1,413 mg/l. The pH concentration at the Krueng Aceh River sampling location has met the quality standards set in PP No. 82 of 2021